A systematic evaluation of links among corporate structure, knowledge management, and financial effectiveness in Vietnam’s banking sector - Huynh, Quang Linh; Nguyen, Nguyen Van (Asian Journal of Economic Modelling, 2024)
There have been a few studies that have examined the moderating importance of corporate structures in the model. Consequently, the key aim of the current research is to investigate the influences of corporate structures on financial effectiveness in banking and knowledge management, where it attempts to evaluate the moderating role of corporate structures on the relationship between knowledge management and financial effectiveness in banking. The current study is based on the population of banks and banking branches in Vietnam. It employs a survey research design and targets 500 banking institutions in Vietnam. However, only 328 appropriate institutions offered sufficiently required information for analyses. The procedures of multiple regressions are applied to statistically investigate causal associations, while the methods of hierarchical regressions were utilized to examine the moderation of corporate structure in the linkages. The research results indicate statistically significant influences of knowledge management and corporate structures on financial effectiveness in banking. More importantly, this study finds that the way corporate structures affect the relationship between knowledge management and how well banks do financially is statistically significant. The empirical findings help administrators make suitable corporate structures that better match the adoption of knowledge management in banking so that they can enjoy enhanced financial effectiveness in banking. This study adds to the literature by evaluating the moderating role of corporate structures in the association between management of knowledge and financial effectiveness in banking. These distinctions improve the field, setting it apart from other research projects.